Understanding the Integration of Deep Learning and Artificial Intelligence in Quranic Education and Research through Bibliometric Analysis - Andri Nirwana An; Fauziyah Qurrota A’yun Tamami; Zainora Daud; Norsaleha Mohd Salleh; Mohamad Haeqal bin Ishak; Muthoifin Muthoifin (Universitepark Limited, 2025)
Indexed by WOS/Scopus/ERA